Unconjugated bilirubin ameliorates the inflammation and digestive protease increase in TNBS-induced colitis - Zhou, Jin-An (Mol Med Rep, 2017)
The authors previously demonstrated that unconjugated bilirubin (UCB) may inhibit the activities of various digestive proteases, including trypsin and chymotrypsin. The digestive proteases in the lower gut are important in the pathogenesis of inflammatory bowel diseases. The effects of UCB on the inflammation and levels of digestive proteases in feces of rats with colitis have not yet been revealed. The present study investigated the effect of UCB on the inflammatory status and levels of trypsin and chymotrypsin in the feces of rats with trinitrobenzenesulfonic acid (TNBS)-induced colitis. The data indicated that treatment with TNBS resulted in a marked reduction in weight gain, which was significantly alleviated in UCB-treated rats. Furthermore, UCB treatment alleviated the inflammation induced by TNBS, detected via macroscopic damage and microscopic inflammation scores, and pro-inflammatory markers including myeloperoxidase (MPO), tumor necrosis factor (TNF)-α and interleukin (IL)-1β. Furthermore, rats with colitis demonstrated significant increases in fecal trypsin and chymotrypsin levels, whereas UCB treatment significantly alleviated these increases. A significant positive correlation was additionally revealed among the pro-inflammatory markers (MPO, TNF-α and IL-1β) and fecal digestive proteases (trypsin and chymotrypsin) in colitis. The results of the present study demonstrated that UCB ameliorated the inflammation and digestive protease increase in TNBS-induced colitis.